The Intersection of Men’s Sexual Violence Perpetration and Sexual Risk Behavior: A Literature Review - Davis, Kelly Cue (Aggress Violent Behav, 2018)
According to the Confluence Model of Sexual Violence, men with a strong impersonal sex orientation (i.e., greater engagement in sexual activities with more casual sexual partners) are at increased risk of perpetrating sexual violence. Research from a variety of countries and samples has supported this proposition, finding that men who perpetrate sexual violence are also more likely to engage in risky sexual behavior. The present article reviews this literature, synthesizing research findings from both psychology and public health domains utilizing both domestic and international samples. In particular, this review focuses on the associations between men’s perpetration of sexual violence and their sexual partners, condom use, and sexually transmitted infection status, as well as provides recommendations for future research directions and prevention and intervention programming.